Pengaruh Harga dan Produk terhadap Kepuasan Pelanggan Wendy's Palembang - Putri Angelica Evelyn; Kevin Antonio Susanto (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to examine the effect of price and product on customer satisfaction at Wendy's Palembang. The technique used for data collection was by distributing questionnaires on a Likert scale, with a total of 116 respondents. The type of research used in this research is a quantitative approach. The sampling technique uses non-probability sampling using the Accidental Sampling technique. This research data processing uses SPSS 26 software. The results of this research show that partially, the price variables (X1 and Product (X2) have a positive and insignificant effect on customer satisfaction. This research shows that all the independent variables used are price (X1) and product (X4) influences customer satisfaction.Keywords: Price, Product, Customer Satisfaction